Burden of Cancers Attributable to Infectious Agents in Nigeria: 2012–2014 - Odutola, Michael; Jedy-Agba, Elima E.; Dareng, Eileen O.; Oga, Emmanuel Aja; Igbinoba, Festus; Otu, Theresa; Ezeome, Emmanuel; Hassan, Ramatu; Adebamowo, Clement A. (Frontiers in Oncology, 2016)
Introduction Infections by certain viruses, bacteria, and parasites have been identified as risk factors for some cancers. In Nigeria, like so many other developing countries, infections remain a leading cause of death. While there is data on the incidence of different cancers in Nigeria, there has been no study of cancers attributable to infections. This study was carried out to determine the burden of cancers associated with infections using data from two Population Based Cancer Registries (PBCRs) in Nigeria. Methods We obtained data on cancers associated with EBV, HPV, hepatitis B and C, HIV, HHV8, H. pylori and Schistosoma spp from the databases of Abuja and Enugu cancer registries in Nigeria. We used PAF for infections-associated cancers in developing countries that are based on prevalence data and relative risk estimates from previous studies. Results The PBCRs reported 4,336 incident cancer cases (ASR 113.9 per 100,000) from 2012 – 2014, of which 1,627 (37.5%) were in males and 2,709 (62.5%) were in females. Some 1,030 (23.8%) of these cancers were associated with infections (ASR 44.4 per 100,000), while 951 (22.0%) were attributable to infections (ASR 41.6 per 100,000). Cancers of the cervix (n=392, ASR 28.3 per 100,000) and liver (n=145, ASR 3.4 per 100,000); and Non-Hodgkin’s Lymphoma (n=110, ASR 2.5 per 100,000) were the commonest infections-associated cancers overall. The commonest infectious agents associated with cancers in this population were HPV, EBV, hepatitis B and C, HIV and HHV8. Conclusion Our results suggest that 23.8% of incident cancer cases in this population were associated with infections while 22.0% were attributable to infections. The cancers which were attributable to infections, are potentially preventable with strategies such as vaccination, risk factor modification or anti-infective treatment.